BIBLIOTECILE ŞI E-GUVERNAREA - OSOIANU, Vera (BIBLIOPOLIS, 2020)
This is an article about the state politic of electronic services in the Republic Moldova. In order to facilite the process and to assure a transparent governance, the Government of the Republic of Moldova set up a eGovernment Centre in August 2010. The 16th of February 2011 the e-Government Centre lanched the web site (http://www.egov.md). The article points out the technological potencial of the public libraries and its limitated possibilities to serve as point of access to information.